An integrated criterion of efficiency for Pt catalysts in the dehydrogenation of higher n-paraffins - Romanovskiy R. V. Rostislav Vladimirovich; Frantsina E. V. Evgeniya Vladimirovna; Youriev Е. M.; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Kravtsov A. V. Anatoly Vasilyevich (2010, 2010)
Title screen